1999
DOI: 10.1046/j.1440-1681.1999.02983.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Denervation Combined With Elimination of Adrenal–renal Portal Circulation Prevents the Development of Hypertension in Spontaneously Hypertensive Rats

Abstract: 1. Kidney denervation in spontaneously hypertensive rats (SHR) during the prehypertensive stage delays and attenuates the development of hypertension. The same results have been obtained after elimination of the adrenal-renal portal circulation (ARPC). The aim of the present study was to investigate the influence of concomitant kidney denervation and elimination of ARPC on hypertension in SHR. 2. Experiments were performed on 6-week-old male SHR and Wistar-Kyoto (WKY) rats. In the first group of animals (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…16 Animal models have demonstrated that renal denervation resulted in decreased sodium and water retention resulting in decreased blood pressures. [17][18][19][20] Finally, rabbit models showed an increase in renal blood flow post renal denervation and rat models demonstrated that wall-to-lumen ratio in renal vasculature was increased in HTN and renal sympathetic denervation reversed this phenomenon demonstrating the significance of sympathetic overactivity in HTN. 21,22 Thus a catheter-based procedure that avoids the serious complications associated with total sympathectomy was devised to target the sympathetic nerves within the renal vasculature.…”
Section: Rationale For Renal Denervationmentioning
confidence: 94%
“…16 Animal models have demonstrated that renal denervation resulted in decreased sodium and water retention resulting in decreased blood pressures. [17][18][19][20] Finally, rabbit models showed an increase in renal blood flow post renal denervation and rat models demonstrated that wall-to-lumen ratio in renal vasculature was increased in HTN and renal sympathetic denervation reversed this phenomenon demonstrating the significance of sympathetic overactivity in HTN. 21,22 Thus a catheter-based procedure that avoids the serious complications associated with total sympathectomy was devised to target the sympathetic nerves within the renal vasculature.…”
Section: Rationale For Renal Denervationmentioning
confidence: 94%
“…The important role of the renal SNS (RSNS) in initiation and maintenance of hypertension has been demonstrated in animal experiments and experience in humans either by measuring its activity in hypertensive subjects or by monitoring BP changes after sympathetic manipulation [10,11] .…”
Section: The Renal Sympathetic Nervous System and Hypertensionmentioning
confidence: 99%
“…modulate renal SNS activity, without disrupting the innervation of other abdominal or pelvic organs. Supported by data from several experimental models of HTN alongside preclinical confirmation of vascular safety and healing response, [31][32][33][34] percutaneous RSDN has emerged as a viable method of abrogating sympathetic hyperactivation.…”
Section: A Novel Application For An Established Conceptmentioning
confidence: 99%